1994
DOI: 10.1063/1.467897
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation and structural study of aniline–methanol mixture using picosecond time domain reflectometry

Abstract: Complex permittivity of aniline-methanol mixture for various temperatures have been measured as a function of frequency between 10 MHz and 10 GHz using time domain reflectometry technique (TDR). Dielectric parameters viz. static dielectric constant c s ' relaxation time r were obtained from complex permittivity spectra using nonlinear least-square fit method. With these parameters, excess dielectric properties, Kirkwood correlation factor and thermodynamic parameters were determined and discussed to yield the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 13 publications
0
9
0
3
Order By: Relevance
“…As it follows from Figure 4, the " 1 value increases with increase in X for both DMSO and DESO. The information related to interaction of liquids A and B may be obtained by excess properties related to the permittivity and relaxation times in the mixture [15][16][17][18]. The excess permittivity " E is defined as:…”
Section: Resultsmentioning
confidence: 99%
“…As it follows from Figure 4, the " 1 value increases with increase in X for both DMSO and DESO. The information related to interaction of liquids A and B may be obtained by excess properties related to the permittivity and relaxation times in the mixture [15][16][17][18]. The excess permittivity " E is defined as:…”
Section: Resultsmentioning
confidence: 99%
“…The dielectric studies on aromatic molecules have been reported from our laboratory earlier [1][2][3][4][5][6][7][8] and others , as dielectric approach forms one of the powerful tools for the determination of molecular structure [9]. For example, in the case of some derivatives of sydnones rather high values of electric dipole moments could be explained in a satisfactory way by assigning cyclic meso-ionic structures rather than an improbable bicyclic structure.…”
Section: Introductionmentioning
confidence: 98%
“…Visco-elastic behaviour and its effect on dielectric relaxation has been reported from our laboratory in the recent past [1][2][3][4] and is a long-perused problem [1][2][3][4][5][6][7][8][9][10], since, in the absence of a perfect empirical or theoretical equation for the variation of dielectric relaxation time with viscosity, the experimental investigations on different systems can only give an insight. These studies throw light on certain quantitative trends and contribute to drawing conclusions regarding molecular motion and intermolecular forces in liquids, liquid mixtures, dilute solutions and multi-component polar solutes in dilute solution .…”
Section: Introductionmentioning
confidence: 99%